SOSIALISASI SISTEM PENDIDIKAN TINGGI INDONESIA PADA PROGRAM ORIENTASI KEGIATAN KAMPUS - Meliza, Meliza (Universitas Mataram, 2025)
The higher education system plays a crucial role in shaping the academic quality and competency achievement of graduates. Socialization of the higher education system for students plays a crucial role in the adaptation process of new students to the academic environment, institutional policies, and opportunities for self-development. Socialization of the higher education system for students is one of the programs in the New Student Campus Activity Introduction Program (PKKMB) of the Faculty of Economics and Business, University of Pekalongan. This activity is carried out in four stages: identification, socialization, discussion, and evaluation of activities. The socialization material covers national higher education standards, undergraduate graduate competencies, the learning process, study period, and tips for successful study in higher education. The results of the activity showed an increase in the participants' understanding of the learning process and campus life. Before the socialization, only 22% of new students understood the higher education system and campus life. After the socialization, this number increased to 76%.